Role and Application of Intravenous High-Dose Vitamin C in Cancer - Junwen OU (Zhongliu Fangzhi Yanjiu)
An increasing number of evidence indicate that intravenous high-dose vitamin C (HVC) is safe to use in patients with various types of cancer. Clinical studies suggest that when used in combination with radiation and chemotherapy, HVC can reduce their toxic side effects and substantially prolong the overall survival of patients. In vitro and animal experiments demonstrated that vitamin C has pro-oxidant cytotoxicity, reverses epithelial-mesenchymal transition, inhibits hypoxia and oncogenic kinase signal transduction, and improves immune function. Although many phase Ⅰ/Ⅱ clinical studies and case reports confirming the adjuvant anti-tumor effects of HVC have been published, large-sample, multicenter randomized controlled phase Ⅲ clinical trial data are still lacking. Therefore, this paper further explores the role and significance of this low-toxicity adjuvant antitumor therapy in clinical use.